2017
DOI: 10.1016/j.jamcollsurg.2017.07.302
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide Does Not Prevent Postoperative Pancreatic Fistula: A Prospective Study

Abstract: income were less educated, treated less, and were more likely to live in rural places, have advanced stages of HCC, and therefore, poorer long-term survival (in total and after surgical resection) than high-income groups. By Cox regression analysis, lower household income was independently associated with poorer outcome (hazard ratio 1.2, 95% CI 1.0e1.4, p ¼ 0.036). CONCLUSIONS: These results indicate that education and income are critically associated with early diagnosis, treatments, and prognosis of HCC. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Elliott et al at the University of California Los Angeles reported 111 consecutive patients who received pasireotide undergoing PD or DP, compared to a historical cohort who did not receive the medication 7 . No differences were detected in the CR‐POPF rate (17.1% pasireotide vs 15.5% control, P = .715) or length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elliott et al at the University of California Los Angeles reported 111 consecutive patients who received pasireotide undergoing PD or DP, compared to a historical cohort who did not receive the medication 7 . No differences were detected in the CR‐POPF rate (17.1% pasireotide vs 15.5% control, P = .715) or length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original publication, a number of concerns regarding the applicability of the data at other centers have been raised, including low usage of surgical drains at MSKCC, the high rate of overall complications in the study, and high rate of POPF reported in the placebo group 5 . These promising results have failed to be replicated in several other single‐institution series 6‐8 which have not shown a reduction in CR‐POPF with pasireotide.…”
Section: Introductionmentioning
confidence: 96%
“…Patient demographics and characteristics were evaluated for differences between groups. Age range from 3 studies 13-15 was converted to estimate SD (Table 1). 19 Three studies defined a dilated pancreatic duct with a diameter >4 mm at the site of transection, 12,13,16 whereas another study defined a dilated duct to be >3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…19 Three studies defined a dilated pancreatic duct with a diameter >4 mm at the site of transection, 12,13,16 whereas another study defined a dilated duct to be >3 mm. 15 The cancer diagnosis was reported in multiple histologies across centers, so it was considered a binary event for this analysis. Pancreatic gland texture was consistently reported with subjective surgeon assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation